Supernova Remnants HB3, 3C58 and IC443 at Decameter Waves - Sidorchuk, M. A.; Abramenkov, E. A. (Видавничий дім «Академперіодика», 2013)
The radio images of the supernova remnants HB3, 3C58 and IC443 obtained with the UTR-2 radio telescope at four frequencies within the 14.7ё25 MHz frequency range are given with the best for this band resolutions 58'ё34', respectively. The flux densities for HB3 and IC443 are determined at frequencies 12.6ё25 MHz, their spectra constructed. At decameter waves these latter have a drop mainly due to absorption in the ioni-zed hydrogen distributed within the remnant for IC443 and, possibly, in the relic HII envelope with the emission measure ~120 pc·cm-6 and the halo of the W3\W4 complex for HB3. At high frequencies, HB3 spectrum is two-component, broaken near 600 MHz and flatter above, with the spectral index 0.3±0.03, while below the frequency break this latter makes 0.57±0.02. The angular size of HB3 (and, possibly, IC443, too) is larger at low frequencies vs. the higher ones and equals 110'x215' at these wavelengths that may be due to existence of the emission with the steep spectrum at the remnant envelope exterior. The spectrum of 3C58 has a drop at frequencies below 38 MHz, though this supernova remnant fails to be reliably identified with the discrete emission at decameter maps.